2020
DOI: 10.1002/hpja.384
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ views on high school food environments

Abstract: Issue addressed This study explored adolescents’ views on high school food environments and potential strategies to help them to make informed food choices. Methods Fifteen focus groups were conducted with 131 adolescents aged 12‐17 years from three high schools in South East Queensland, Australia. Adolescents were asked how their school food environment (dis)encouraged them to eat healthy and what schools could do to help them eat healthier. All focus groups were audio recorded. Data were analysed using conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 43 publications
1
19
0
1
Order By: Relevance
“…Enjoyment of physical activity with others and eating cultural foods were powerful motivators for action. Findings from this study are in agreement with earlier studies, which identify determinants of adolescents’ food choices include food cravings, convenience, social support from friends and family, availability of nutritious versus less healthy foods at home, influence of social media on body image, as well as having health and fitness goals [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Enjoyment of physical activity with others and eating cultural foods were powerful motivators for action. Findings from this study are in agreement with earlier studies, which identify determinants of adolescents’ food choices include food cravings, convenience, social support from friends and family, availability of nutritious versus less healthy foods at home, influence of social media on body image, as well as having health and fitness goals [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, adolescents in this study reported a higher consumption of unhealthy foods when at school. This could be explained by the findings of a recent Australian study, declaring a lack of healthy food options in high schools [ 26 ]. Earlier studies have emphasised the importance for future prevention programs to collaborate with stakeholders within the community (i.e., ME community) to provide environmental and interpersonal support [ 33 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, among US adolescents, taste, hunger and convenience were reported as more influential on their dietary choices than the perceived health benefits of foods (6) . Similarly, in a study with Australian adolescents, food appeal and price were reported to take precedence over the healthiness of the items when purchasing foods in schools (58) . Moreover, evidence suggests that adolescents' have a low-risk perception of the consequences of consuming an unhealthy diet during their life stage (6,7,32,51,52,59) , and thus, view consuming a healthy diet more important in the future (6) , when health is considered of more relevance (55) .…”
Section: Impact Of Nutritional Knowledge On Adolescents' Dietary Choicesmentioning
confidence: 92%
“…Both early and more current research indicates that adolescents across several countries possess a good level of nutritional knowledge (7,(51)(52)(53)(54)(55) and have awareness on both the short and longterm consequences to their health of not consuming a nutritious diet (7,52,54) . However, it has been highlighted that this level of nutritional knowledge does not always translate into their behaviours and actual choice of food (54,56) and nutrition is often not a primary consideration when making their dietary decisions (51,57,58) , with other competing factors which can grant more instant gratification, such as taste, appearance, price and convenience, often taking priority (6,51,58) . For example, among US adolescents, taste, hunger and convenience were reported as more influential on their dietary choices than the perceived health benefits of foods (6) .…”
Section: Impact Of Nutritional Knowledge On Adolescents' Dietary Choicesmentioning
confidence: 99%
“…Consideramos que las intervenciones como restringir la disponibilidad de este tipo de alimentos y bebidas en los centros educativos y sus alrededores, así como incrementar las tasas de los mismos podrían ser efectivas para disminuir su consumo, como también concluyen en otros estudios consultados (334). En el estudio de Ronto et al (335), son los propios adolescentes los que refieren que el entorno alimentario del centro educativo no ayuda a elegir alimentos saludables y proponen limitar los alimentos poco saludables e incluir clases de educación nutricional obligatorias. Asimismo, se debe trabajar con las familias para reducir la disponibilidad de refrescos en casa, de forma que no estén al alcance del adolescente en cualquier momento y el hogar sea el primer lugar de ejemplo para la reducción de su consumo.…”
Section: Vii12 Alimentaciónunclassified